Translation and evaluation of a Chinese version of the Child Oral Health-related Quality of Life measure - COLMAN McGRATH , HARRY N. PANG,EDWARD C. M. LO, NIGEL M. KING, URBAN HÄGG & NABIL SAMMAN (IAPD and Blackwell, 2008)
The importance of international collaborative dental research in paediatric dentistry is without question. This has brought with it a need for international instruments for outcome assessment.